COWPEA SEEDS (Vigna unguiculata L. (Walp), TREATED WITH NIM LEAF EXTRACT (Azadirachta indica A. Juss.) AVALIATION OF GERMINATION AND FUNGI INCIDENCE - Campos SILVA, Vânia; Pereira GOMES, Delineide; SANTOS, Ceália Cristine (Scientia Agraria, 2011)
This study aimed to evaluate the effect of aqueous extract of neem on germination and fungi incidence on seeds ofthree cultivars (Serrinha, BR 17 and Maranhão) of cowpea. Neem leaves were dryed, crushed and prepared dilutions of 0.5;1.0; 2.0, 4.0 g dm-3 and control. The fungi incidence was evaluated by the test filter paper and germination according to theRules for Seeds Testing (Regras para Análise de Sementes). In the three cultivars analyzed, reduction in the incidence ofAspergillus sp and Fusarium sp was observed. In relation to the influence of extracts of neem leaves on seed germination,significant effect of extract in Maranhão cultivar was observed, where all concentrations differed from the control, andpropovided a considerable increase in the percentage of normal seedlings. It was concluded that the leaf extract of neem waseffective in controlling Aspergillus sp, Fusarium sp , Phoma sp and Macrophomina phaseolina at different concentrations indifferent cultivars and seed germination was stimulated for the Maranhão cultivar.